Catalytic dehydroaromatization of n-alkanes by pincer-ligated iridium complexes - Ahuja, Ritu; Punji, Benudhar; Findlater, Michael; Supplee, Carolyn; Schinski, William; Brookhart, Maurice; Goldman, Alan S. (Nature Chemistry, 2011)
Aromatic hydrocarbons are among the most important building blocks in the chemical industry. Benzene, toluene and xylenes are obtained from the high temperature thermolysis of alkanes. Higher alkylaromatics are generally derived from arene–olefin coupling, which gives branched products—that is, secondary alkyl arenes—with olefins higher than ethylene. The dehydrogenation of acyclic alkanes to give alkylaromatics can be achieved using heterogeneous catalysts at high temperatures, but with low yields and low selectivity. We present here the first catalytic conversion of n-alkanes to alkylaromatics using homogeneous or molecular catalysts—specifically ‘pincer’-ligated iridium complexes—and olefinic hydrogen acceptors. For example, the reaction of n-octane affords up to 86% yield of aromatic product, primarily o-xylene and secondarily ethylbenzene. In the case of n-decane and n-dodecane, the resulting alkylarenes are exclusively unbranched (that is, n-alkyl-substituted), with selectivity for the corresponding o-(n-alkyl)toluene.